KONSEP PEMIKIRAN FAZLUR RAHMAN TENTANG MODERNISASI PENDIDIKAN ISLAM DAN RELEVANSINYA TERHADAP PENDIDIKAN ISLAM DI INDONESIA - Prayitno, Hadi; Qodat, Aminul (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2019)
This study focuses on the theme of the modernization of Islamic education by reintroducing a Muslim intellectual in the repertoire of Islamic thought in modern era, Fazlur Rahman, a Muslim scholar who positioned himself in the Neo-modernist group. This type of research is library research, with a descriptive-qualitative approach, a research methods that aim to describe in full and in depth about social reality and various phenomena that occur in society. The results showed that the Fazlul Rahman's idea of the modernization of Islamic education was motivated by his anxiety about the development of Islamic education which was increasingly left behind and tended to be stagnant. According to Rahman this is due to the many problems in Islamic education, such as: 1) the purpose of education that is not directed in a positive, education tends to be incentive, 2) the existence of educational dichotomy 3) low quality of students, 4) lack of quality and professional educators 5) and the limited Islamic literature available in several libraries and educational institutions. Through his ideas, he tried to renew Islamic education by not forgetting the classical heritage of Muslims. His criticism is directed at the orientation of Islamic education which should not only focus on the needs of the world or the hereafter, but must be both, the world and the hereafter. The contribution of thought and renewal of Islamic education that has been inscribed by Fazlur Rahman has been widely applied in various countries, including in Indonesia.Â Keywords: Fazlur rahman, Modernization, Islamic Education